Perceived Graduates’ Employability in the 4IR Era: Assessing Predictors’ Impacts - Foluso Philip ADEKANMBI; Wilfred Isioma UKPERE (Expert Journal of Business and Management, 2023)
This paper assesses the impacts of perceived proactive career behaviors (PCB), Work-integrated learning effectiveness (WILE), and abilities (AB) on perceived graduates’ employability (PGE) within Nigeria’s businesses in the 4IR era. The sample used in this study came from First City Monument Bank Plc, Isoglass Industries Nigeria Ltd, Honeywell Flour Mills Plc, CohoTek IT Solutions, and Freezeland Nigeria Limited. These are the five examined businesses. They belong to the manufacturing, sales, information technology, and finance sectors. The cross-sectional questionnaire approach was used in this study, and surveys were distributed at random. Nonetheless, 486 of the 500 distributed surveys were located, deemed suitable for use, and subjected to Statistical Packages for Social Sciences analysis (SPSS version 28). This study indicated a considerable individual and collective impact of perceived proactive career behaviors, Work-integrated learning effectiveness, and abilities on perceived graduates’ employability within Nigeria’s businesses in the 4IR era. Businesses and higher education management are urged to investigate and model the most suitable proactive career practices in the current 4IR period. They should also consistently include and encourage work-integrated learning and support due to the sensitive nature of students' understanding of the workplace and requirements inspired by the fourth industrial revolution. Further, managers and leaders in higher education and the workplace should promote and motivate performance abilities appropriate for the current industrial revolution.